2021
DOI: 10.52711/2321-5836.2021.00013
|View full text |Cite
|
Sign up to set email alerts
|

A Review an Isatin, Isatin Derivatives and their Pharmacological Activity

Abstract: Isatin or 1H-indole-2, 3-dione is an indole derivative. Isatin is an important class of heterocyclic compounds. Recently, heterocyclic compounds analogues and their derivatives have attracted strong interest in medicinal chemistry due to their biological and pharmacological properties. The structure have offered a high value of diversity that is proven useful for the development of new medicinal drugs and improved potency,less toxicity and good pharmacological activity. Isatin has a wide varity of pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Research studies have demonstrated that vanillin is effective in prevention and treatment of cognitive impairment and is a good candidate to be used clinically [ 24 ]. Beula et al has reported Isatin (SWA) derivatives with anti-amnesic action [ 25 , 26 ]. In a number of studies vanillin Schiff bases have been found to have potent antioxidant and anticholinesterase activities (both in in-vitro and in-vivo studies).…”
Section: Introductionmentioning
confidence: 99%
“…Research studies have demonstrated that vanillin is effective in prevention and treatment of cognitive impairment and is a good candidate to be used clinically [ 24 ]. Beula et al has reported Isatin (SWA) derivatives with anti-amnesic action [ 25 , 26 ]. In a number of studies vanillin Schiff bases have been found to have potent antioxidant and anticholinesterase activities (both in in-vitro and in-vivo studies).…”
Section: Introductionmentioning
confidence: 99%
“…[9] Isatin serves as a versatile platform for structural modifications, allowing alterations at various positions in its molecular structure, including N-, C2-, C3-, and aromatic rings, for exploring its pharmacological prospective against various diseases. [10,11] Due to its simplicity towards the synthesis and further diverse biological activities exhibited by its derivatives-ranging from antibacterial and anticancer to antiviral and analgesic properties [12][13][14][15][16][17][18][19] isatin holds a prominent place in medicinal chemistry. Its unique molecular structure enables easy modifications, as it can act both as an electrophile and a nucleophile, making it a valuable building block in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its simplicity towards the synthesis and further diverse biological activities exhibited by its derivatives–ranging from antibacterial and anticancer to antiviral and analgesic properties [12–19] isatin holds a prominent place in medicinal chemistry. Its unique molecular structure enables easy modifications, as it can act both as an electrophile and a nucleophile, making it a valuable building block in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%